Art Therapy, Community Building, Activism, and Outcomes - Feen-Calligan, Holly; Moreno, Julie; Buzzard, Emma (Frontiers in Psychology, 2018)
This article is a descriptive study of two groups who came together through a service-learning assignment: The first group is art therapy students enrolled in a research class who worked with six community agencies to help them prepare for undergraduate service-learning placements in an upcoming semester; they also assisted the agencies with program evaluation. The second group is the six community agency directors who were planning for service-learners enrolled in an art history class titled Art as A Social Practice. Service-learning is an experiential learning pedagogy where community service is integrated into an academic course, and where the services performed meet genuine community needs. The hyphen in service-learning represents the ideal that both students and community agencies experience benefits from the relationship, although in reality, it is often the experiences of the students rather than the agencies who help prepare them that receive greater attention in the scholarly research and literature. The present article places focus on the community agencies who, in the process of meeting with arts faculty to plan a service-learning course, made two unexpected requests: First they expressed their strong desire for student placements that were longer than one semester, and secondly, they all requested assistance with evaluating the effectiveness of their programs. This article is about the efforts to respond to these requests through the assistance of art therapy research students. With growing trends in community-based art therapy practice, greater attention to the community agencies where art therapists work is necessary and valuable to art therapy preparation. The present article describes six distinctive communities, illustrating new frontiers of practice. The research students’ experiences and the experiences of the community partners were assessed using qualitative methods that included pre and post questionnaires, written reflections of students, interviews of agency directors and agency/student/researcher focus group transcripts. This study will inform other art therapy programs who may want to use a service-learning approach to teaching research. A discussion of the promising practices of service-learning and research, as well as some challenges leads to recommendations for art therapy education.